Redox Polymers as Electrode-Active Materials for Batteries - Esser, Birgit (Organic Materials, 2019)
Organic cathode materials are promising candidates for a new generation of ‘green batteries’, since they have low toxicity and can be produced from renewable resources or from petroleum. This review shows that organic redox polymers can show excellent battery performance regarding cycling stability and rate capability, and attractive specific capacities are accessible. Radical polymers and redox polymers based on heteroaromatics demonstrate superior rate capabilities and cycling stabilities at fast C-rates as well as high discharge potentials of 3–4 V versus Li/Li+, while quinone- or imide-based polymers deliver high specific capacities of up to 260 mAh g−1 with stable cycling at moderate C-rates and lower discharge potentials. This review article highlights the underlying design principles showcasing selected examples of well-performing redox polymers.
Keywords: organic batteries; redox polymers; cathode materials; fast charging; transition metal-free; high cycling stability